PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA MENGGUNAKAN METODE DRILL/LATIHAN DENGAN BANTUAN MEDIA VISUAL PADA MATAKULIAH KONSEP TEKNOLGI INFORMASI - Hakiki, Muhammad; Sefriani, Rini (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This research is motivated by the low critical thinking ability of students in the learning process and the low desire of students to improve their thinking skills to explore information. The purpose of this study was to describe students' critical thinking skills using the Drill/exercise method with the help of visual media in the information technology education study program. This research is a type of classroom action research which is carried out in two cycles, one cycle with two meetings. Each cycle consists of planning, implementing, observing and reflecting. This research was conducted in the odd semester of the 2020/2021 academic year in the information technology concept course. The research data were collected through qualitative and quantitative data analysis techniques. The results of data analysis showed that the drill/practice method with the help of visual media in learning could improve students' critical thinking skills in the information technology concept course. the results of the teacher's observations in the first cycle of the first meeting with a percentage of 75% for the second meeting 83.33% and in the second cycle of the first meeting 83.33% for the second meeting 91.66% with a very good category. The results of student observations in the first cycle at the first meeting with a percentage of 40% for the second meeting 66.66% and the second cycle of the first meeting 73.33% for the second meeting 80%. While classical completeness in the first cycle obtained the average value of students' critical thinking skills of 46.66% increased to 53.33% in the second cycle. It is concluded that the use of the Drill/exercise method with the help of visual media can improve students' critical thinking skills in the information technology concept course.